Promoting collaboration between health science disciplines at the university of alberta, canadá - Genevieve Gray (Texto & Contexto Enfermagem, 2005)
Interdisciplinary education, research and practice, improves health care, scholarly productivity,professionals career opportunities and patients/clients and health professionals satisfaction with care andwork, respectively. However, it can engender disinterest, suspicion and antagonism if it is not adequatelyresources. Adequate resourcing requires both highly visible commitment from the key leaders in universitiesand health services and separate, realistic budgets to support initiatives. In addition, and to ensure that thespecialist contribution of all health disciplines to human well-being is fostered the practice, research andeducation of specialist disciplines must also be adequately supported. This is what the Health SciencesCouncil at the University of Alberta since its inception - tried to do. That it has been successful is reflectedin its recognition as national leader in interdisciplinarity in health education and research in Canada.